2014
DOI: 10.1002/ijc.29176
|View full text |Cite
|
Sign up to set email alerts
|

Improving cervical cancer screening attendance in Finland

Abstract: High attendance is essential to cervical cancer screening results. Attendance in the Finnish program is currently at 70%, but extensive opportunistic screening occurs beside the organized. A shift from opportunistic to organized screening is imperative to optimize the costs and impact of screening and minimize potential harms. We evaluated the effect of reminder letters (1st reminder) and self-sampling test (2nd reminder) on program attendance. The study population consisted of 31,053 screening invitees in 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 35 publications
(44 reference statements)
7
44
3
1
Order By: Relevance
“…An additional analysis showed that the participation rate in screening for cervical cancer among Korean women aged 15–80 was 58.6%. This is extremely low compared with those observed in other developed countries; for example, the screening rate is approximately 82.9% in the USA,21 80% in the UK22 and 70% in Finland 23. Other studies from Asia suggest that participation in screening for cervical cancer is low (42.1% in Japan, 2013, 52.9% in Taiwan, 2006) 24…”
Section: Discussionmentioning
confidence: 79%
“…An additional analysis showed that the participation rate in screening for cervical cancer among Korean women aged 15–80 was 58.6%. This is extremely low compared with those observed in other developed countries; for example, the screening rate is approximately 82.9% in the USA,21 80% in the UK22 and 70% in Finland 23. Other studies from Asia suggest that participation in screening for cervical cancer is low (42.1% in Japan, 2013, 52.9% in Taiwan, 2006) 24…”
Section: Discussionmentioning
confidence: 79%
“…The number of immigrants including females in Finland has increased in recent years [27]. Previous studies in Finland revealed lower participation rates for cervical cancer screening among immigrants compared with the general Finnish population [28]. To date, however, the reasons for this low participation have been unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the intervention in our study are similar or somewhat larger than these previous findings. More recently, Finnish municipalities using scheduled appointments were reported to achieve a twofold participation after the second reminder compared with municipalities using open reminders 13. Different settings and time periods may influence the impact of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Significant pooled effects on participation (RR 1.5) of scheduled appointments in cervical cancer screening were reported in a systematic review covering three randomised studies 9. More recently, a Finnish report compared municipalities using scheduled and open second reminders and found a twofold difference in participation 13. Other screening programmes have also benefited from scheduled appointments; a non-randomised study from the UK breast cancer screening programme reported participation rates almost three times higher among women receiving timed second reminders 14…”
Section: Introductionmentioning
confidence: 99%